Hydronephrosis Classifications: Has UTD Overtaken APD and SFU? A Worldwide Survey - Vallasciani, Santiago; Bujons Tur, Anna; Gatti, John; Machado, Marcos; Cooper, Christopher S.; Farrugia, Marie Klaire; Zhou, Huixia; El Anbari, Mohammed; Lopez, Pedro-José (Frontiers in Pediatrics, 2021)
Objective: to collect baseline information on the ultrasonographic reporting preferences. Method: a 13-multiple choice questionnaire was designed and distributed worldwide among pediatric urologists, pediatric surgeons and urologists. The statistical analysis of the survey data consisted of 3 steps: a univariate analysis, a bivariate and a multivariate analysis Results: 380 participants responded from all the continents. The bivariate analysis showed the significant differences in the geographical area, the years of experience and the volume of cases. Most of the physicians prefer the SFU and APD systems because of familiarity and simplicity (37 and 34% respectively). Respondents noted that their imaging providers most often report findings utilizing the mild-moderate-severe system or the APD measurements (28 & 39% respectively) except for North America (SFU in 50%). Multivariate analysis did not provide significant differences. Conclusion: Our study evaluates the opinions regarding the various pediatric hydronephrosis classification systems from a large number of specialists and demonstrates that there is no single preferred grading system. The greatest reported shortcoming of all the systems was the lack of universal utilization. The observations taken from this study may serve as basis for the construction of a common worldwide system. As APD and SFU are the preferred systems and the UTD a newer combination of both, it is possible that with time, UTD may become the universal language for reporting hydronephrosis. This time, based on the result of this survey, seems not arrived yet.